Context as a Pre-Condition for Meaning Fixation in Legal Texts: A Pragma-Contextual Analysis of Human Right Treaty-Based Legislative Text - Ajenifari Joshua Taiwo; Awolope Joseph Alaba; Jelili Adewale Adeoye (LingLit Journal Scientific Journal for Linguistics and Literature, 2023)
The imperativeness of contextual nuances to textual meaning fixations has largely remained incontrovertible among scholars across various disciplines, though what counts as context may remain debatable. This paper explored the application of the relevant aspects of Lawal’s (2003) pragmatic theory to foreground the contextual inevitability to meaning processing of the treaty-based legislative text of the Universal Declaration of Human Rights document of 1948 as adopted by the United Nations. The research adopted a qualitative approach of analysis with a view to experimenting the applicability of language-based theory of pragmatics to the explication of legal-based text. The research showed that legal texts, as products of linguistic deployments, are not only subject to the context of human conditions, but are also amenable to the application of context-based theory of natural language. It was revealed that the linguistic deployments in any communicative legal text is a function of non-linguistic factors of context such as sociological, historical, psychological, social and cosmological situations of the human parties to the ensuing legal contracts under the circumstance